Efektivitas Project Based Learning Berbasis Ict Terhadap Kemampuan Critical Thinking Mahasiswa Efl - Ance Jusmaya; Winda Evyanto (Prosiding, 2018)
This research is based on the findings of the previous studies which show that there are still low quality of Critical Thinking of students. Therefore, it is necessary to apply ICT-based learning as well as to optimize the Critical Thinking ability of the students. One of the learning method in the 21st century is the Project Based Learning based ICT. The purpose of this study is to solve the problem concerning the are still low quality of Critical Thinking students as well as the problems faced by lecturers who teach in universities in Batam.This is a quasi-experimental research that want to find out the efectivenes of Project Based Learning bsed ICT towards Criical Thinking of EFL students in Batam. An eexperimental class is given a treatment used Project Based Learning based ICT with critical thinking theory. Then, control class is given a treathment used conventional method with critical thinking theory Then the researcher calculated the data using the normality test. The normality of control class L observed <L table (0.099 <0.165) and in the experimental class (0.133 <0.162). Thus, it can be concluded that all data is normally distributed. Then the homogeneity test is conducted where F observed is <F table (1.20 <1.88. So it can be concluded that all data is homogeneous. The last is the hypothesis test where T observed> T table (7.50> 2.00). Therefore, it can be concluded that the proposed hypothesis is accepted. Thus Project Based Learning based ICT method has a significant influence on the Critical Thinking ability of EFL students in Batam